Asymmetric Shifts in Precipitation Alter Nitrogen Use Strategies in Global Croplands - Jinglan Cui; Yujing Gao; Luxi Cheng; Xi Zhang; Ouping Deng; Miao Zheng; Zhongrui Xie; Hans J. M. van Grinsven; Lorenzo Rosa; Baojing Gu (Global Change Biology, 2026)
Global warming intensifies regional precipitation imbalances that disrupt cropland nitrogen cycling and threaten food security. Here, we show that global croplands respond asymmetrically to future precipitation change. Under a middle of the road scenario for 2050, 78% of croplands are projected to become wetter, increasing yields by 15% but raising nitrogen losses by 45%. The remaining 22% that become drier would experience a 29% decline in yields and a 25% rise in nitrogen losses. Nitrogen use efficiency declines by 3%–14% worldwide because both wetter and drier conditions reduce plant uptake or accelerate losses. Although altered precipitation increases global crop production by 8%, the accompanying 43% rise in nitrogen losses may compromise long term sustainability. Subtropical and tropical regions between 30° N and 30° S emerge as disruption hotspots. Adaptation measures such as optimized fertilizer management and adjusted planting dates could mitigate up to 462 billion USD per year in damages linked to nitrogen losses. These results highlight the need for adaptive strategies to secure food production and environmental sustainability under asymmetric precipitation change.